2004
DOI: 10.1016/j.jtcvs.2003.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cerebral and somatic oxygenation during stage 1 palliation of hypoplastic left heart syndrome using continuous regional cerebral perfusion

Abstract: Cerebral oxygenation was maintained during regional cerebral perfusion at prebypass levels with deep hypothermia. However, after rewarming and separation from cardiopulmonary bypass, cerebral oxygenation was lower compared with prebypass or somatic values. These results indicate that cerebrovascular resistance is increased after deep hypothermic cardiopulmonary bypass, even with continuous perfusion techniques, placing the cerebral circulation at risk postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(145 citation statements)
references
References 44 publications
(71 reference statements)
9
133
0
1
Order By: Relevance
“…In several studies, reduced cerebral oxygenation values were reported to be caused by several reasons, such as cardiac manipulation, dissection of surrounding tissues, pericardial suspension, and cannulation of vena cava and aorta, particularly during the pre-bypass period. [17][18][19] In the present study, cerebral oxygenation data of the pre-and post-bypass periods were similar in all time points in both groups.…”
Section: Discussionsupporting
confidence: 67%
“…In several studies, reduced cerebral oxygenation values were reported to be caused by several reasons, such as cardiac manipulation, dissection of surrounding tissues, pericardial suspension, and cannulation of vena cava and aorta, particularly during the pre-bypass period. [17][18][19] In the present study, cerebral oxygenation data of the pre-and post-bypass periods were similar in all time points in both groups.…”
Section: Discussionsupporting
confidence: 67%
“…8 Non-invasive near-infrared spectroscopy (NIRS) technology that has been used to assess neonatal regional tissue oxygenation was utilized to measure oxygenation in cerebral, renal and mesenteric tissue. 9,10,11 The results of this study will add to our knowledge with regard to the role of the PDA in regional tissue oxygenation.…”
Section: Introductionmentioning
confidence: 75%
“…This group was the first to prove that the brain was oxygenated during this technique, and also demonstrated both blood pressure and flow to the subdiaphragmatic viscera during this technique via the extensive system of collateral arterial supply in neonates. This flow and oxygenation to the lower body is lower than normal bypass flows (13), but nonetheless demonstrates another potential advantage of ACP over DHCA. As detailed elsewhere in this monograph, cannulation technique is critical, because other techniques of ACP cannulation involving direct cannulation of the right innominate artery, with snaring that excludes the subclavian-vertebral artery, could theoretically result in less perfusion to the brain.…”
Section: Details Of Acp Techniquementioning
confidence: 87%